Urinary tract infections in children with cancer and febrile neutropenia – single center experience - Kovač, Nataša; Samardžić Lukić, Maja; Kaćanski, Nataša; Kovač, Aleksandra; Latinović, Tijana; Kolarović, Jovanka (Vojnosanitetski pregled, 2024)
Background/Aim. Urinary tract infection (UTI) in children with febrile neutropenia (FN) after receiving chemotherapy could be followed by atypical symptoms and signs. The absence of routine urine culture (UC) sampling for analysis could lead to undiagnosed disease and inadequate treatment of these patients. The aim of the study was to indicate the importance of sampling UC in children who have developed FN and to point out the most probable causative agents of UTI in children with FN and antibiotic sensitivity/resistance of the isolated strains. Methods. During a five-year observation period, 40 UTIs were registered in 30 patients with FN. In the study group of patients with FN, the number of UTIs, the number of recurrent UTIs, isolated pathogens, their sensitivity to antibiotics, characteristics of urine sediment, the presence of localized symptoms of UTI, and the presence of urosepsis were analyzed. The obtained results were compared with the control group which consisted of children who were healthy prior to hospitalization due to febrile urinary infection. Results. When compared to the control group, significant differences in the presence of symptoms of UTI and urine sediment findings in patients with FN were observed. A higher percentage of resistant strains of Escherichia coli isolated from UC of cancer patients with FN was noted when compared to the control group. Three UTI cases were followed by urosepsis. Conclusion. UC findings are important not only in establishing the diagnosis of UTI and detecting multi-resistant bacterial strains but also in choosing appropriate antibiotics and selecting a subgroup of patients with recurrent UTI who require further monitoring and detecting potential complications in a timely manner.